Efficacy and Safety of Pericapsular Nerve Group Block for Hip Fracture Surgery under Spinal Anesthesia: A Meta-Analysis - Shukai Li; Jing An; Chengyu Qian; Zhixue Wang (International Journal of Clinical Practice)
Objective. To evaluate the effectiveness and safety of pericapsular nerve group (PENG) block for hip fracture surgery under spinal anesthesia. Methods. This meta-analysis was registered on INPLASY (INPLASY202270005). PubMed, Embase, Cochrane, CNKI, and Wanfang databases were searched to collect the randomized controlled trials of the PENG block applied to hip fracture surgery in the setting of spinal anesthesia, with the search period from inception to 1 May 2023. Two independent researchers gradually screened the literature, evaluated the quality, extracted the data, and eventually pooled data using RevMan 5.4. Results. Fifteen articles with 890 patients were enrolled. The combined results showed that the PENG block reduced pain scores during position placement (SMD = −0.35; 95% CI [−0.67, 0.02]; P=0.04; I2 = 0%). Subgroup analyses showed that compared to the unblocked group, the PENG block reduced pain scores at 12 h, 24 h, and 48 h postoperatively. The incidence of postoperative hypokinesia was reduced (RR = 0.11; 95% CI [0.01, 0.86]; P=0.04; I2 = 0.00%). The time to first walking was advanced (SMD = −0.90; 95% CI [−1.17, 0.63]; P<0.00001; I2 = 0%). Conclusion. The PENG block can reduce postoperative pain and pain during spinal anesthesia positioning, which is helpful to improve the operability and comfort of spinal anesthesia and facilitate postoperative muscle strength recovery and early activity.